URGENSI MANAJEMEN TALENTA DALAM UPAYA PERCEPATAN TRANSFORMASI ORGANISASI PUBLIK - Eny Suryani; Titi Stiawati (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
The most important resource for organizations is people so organizations must be able to manage them. One approach to managing Human Resources is Talent Management. Talent management is a process that involves identifying, managing, and developing individual capabilities based on organizational needs. This article discusses the importance of implementing talent management in an effort to accelerate the transformation of public organizations. This research is a type of qualitative research that uses a literature study approach. The results show that the urgency of implementing talent management in an effort to accelerate the transformation of public organizations is to increase the productivity and effectiveness of public organizations, improve the quality of public services, increase organizational competitiveness, as a source of innovation and development, increase employee satisfaction and readiness to face change.